Analysis on the applicability of modified polyvinyl alcohol (MPA) for temporary controlling the dust from soil in construction site. (3rd April 2021) - Li, Min; Du, Hongpu; Zhou, Lang; Chai, Shouxi; Wang, Min
ABSTRACT: Dust from construction field is one of sources for the atmosphere particulate pollution. In this study, a solidifying material, modified polyvinyl alcohol (MPA), is used to control the dust from soil. The controlling efficiency of the MPA is evaluated based on its anti-wind and anti-rain erosion performance under different conditions such as soil types, spraying amount of MPA, slope morphologies (gradients and unevenness), and treated time. Results indicate that the MPA can bind well with the soil particles and it is able to strengthen the integrity of the surface. Soil treated with MPA exhibits good anti-wind effects, and PM10 and PM2.5 in environment do not increase even under a nine-grade wind erosion. Soil treated with MPA can maintain the surface integrity under a rainstorm, and there are no erosion traces and mud after rain erosion. The application of MPA has no limitation in terms of soil type, soil slope, and surface morphology, and thus, it has a wide applied prospect in engineering. Implications: In order to solve the air pollution problems existing on construction sites in densely populated areas, MPA optimizes a kind of environmental agent to treat, which does not affect the later use of soil. The applicability effect was verified from the perspective of anti-wind and anti-rain erosion doubly. Research results not only can provide data support for the construction management, but also help to promote the civilization and ecological benefit of construction.